Effect of Web-Based Problem Based Learning on School Administrators' Self-Efficacy Beliefs and Attitudes Towards Principalship Profession - Karabatak, Songul; Turhan, Muhammed (Turkish Education Assoc, 2017)
The purpose of this research is to determine the effect of a web based problem based school administrator training program (WB-PBSAT) on participants' self-efficacy beliefs and attitudes towards principalship. For this aim, mixed approach combining quantitative and qualitative research approach was used in this study. The quantitative dimension was carried out with the experimental model. The focus group interviews were conducted in the qualitative dimension. An experimental group and a control group were used. Participants of the experimental and the control groups were determined by purposive sampling. According to the findings, WB-PBSAT process was significantly and positively affected participants' attitudes towards general and professional self-efficacy beliefs and principalship. This result shows that the administrator training model used has the potential to make significant contributions in the professional development of school administrators.
Keywords: School administrator training; Web based learning; Problem based learning; Self-efficacy belief; Attitude toward principalship